The Concept of Causality and Teleology in Aristotle's Philosophy and its Impact on the Foundation of Scientific Thinking in Greek Philosophy: An Analytical Philosophical Reading (Al-Farooq Journal of Sciences, 2026)
The research examined the concepts of causality and teleology in Aristotle’s philosophy and their role in founding scientific thinking in Greek philosophy. It showed that Aristotle did not understand cause in the narrow sense of a direct cause only, but regarded it as a comprehensive explanatory principle based on four causes: material, formal, efficient, and final. The research also clarified that teleology represents a fundamental element in explaining nature and motion, as beings, according to Aristotle, move from potentiality to actuality toward their proper form and perfection. The study concluded that science for Aristotle is not based merely on observing phenomena, but on knowing their causes and principles through demonstration, syllogism, and induction. Thus, Aristotle’s conception of causality and teleology contributed to establishing an organized form of scientific thinking based on explaining natural existence, motion, and purpose.
Keywords: Causality, teleology, Aristotle, four causes, scientific thinking, Greek philosophy